EFFECTIVENESS OF DIRECT CASH ASSISTANCE VILLAGE FUNDS FOR COMMUNITIES AFFECTED BY COVID-19 IN PULOREJO VILLAGE, DAWARBLANDONG DISTRICT, MOJOKERTO REGENCY - David Yoel Geovano; Tukiman Tukiman (DIA: Jurnal Administrasi Publik, 2021)
At the beginning of 2020, an outbreak of the Covid-19 disease emerged from China and spread rapidly throughout the world. The world government continues to strive to overcome the spread of the Covid-19 virus and also its impact, one of the impacts of Covid-19 is on the economic sector. In Indonesia, the community's economy has declined, causing the poverty rate to increase during the pandemic. One of the efforts of the Indonesian government is to make changes to the budget. One of the changes made is the village fund. Village funds initially used for village development and development were transferred as a direct cash assistance budget for village funds. the implementation of the program in terms of its effectiveness still invites many questions. Therefore, this study was conducted to determine the effectiveness of the village fund cash transfer program. The type of research used is qualitative research with data collection techniques of observation, interviews, and documentation. The focus of this research is the effectiveness of the Village Fund Direct Cash Assistance (BLT) program in Pulorejo Village, Dawarblandong District, Mojokerto Regency. Sources of data used are primary data and secondary data. This research was conducted in Pulorejo Village, Dawarblandong District, Mojokerto Regency. The research findings show that the effectiveness of the village fund cash transfer program, especially for the poor and communities affected by Covid-19, has slightly helped their economy, people expect programs like this to continue as long as the pandemic is not over.